Supervision of Student Organization Funds: An Academic Reality - Albertus Febri Christyawan; Aprina Nugrahesthy Sulistya Hapsari (Association of Certified Fraud Examiners Indonesia Chapter, 2021)
This study aims to describe the supervision function of student organization fund management by the student executive and legislative bodies at Faculty X, University ABC. Data are obtained through in-depth interviews with several informants, such as the committee and functionaries of student organization. The results of this study show that the supervision function of student organization fund management has not been running optimally due to several factors. Those factors are found at each phases of student organization fund management. In planning phase, price standardization has not been updated for few periods, which is a constraint in determining the nominal budget. Furthermore, in implementation phase, the legislative institution is not directly involved in disbursing and spending student organization funds. Moreover, validity checking of expenditure evidences in the accountability phase is limited to seeing the completeness of the bills and receipts identities only, without making confirmation to the bills and receipts issuer.